The Role of Amil Zakat Institutions in the Development of Economic Da'wah (Study on Distribution of Zis Funds through the Bankziska Program in Ponorogo) - Adib Khusnul Rois; Azid Syukroni; Nurul Abidin (Perisai : Islamic Banking and Finance Journal, 2022)
The role of the Amil Zakat institution is very much needed in society, many Amil Zakat institutions have the passion to provide assistance to the community by making moral and material contributions. One of the Amil Zakat institutions in Ponorogo is Bank Ziska or stands for financial assistance from zakat funds, infaq-shodaqoh and other religious social funds. The funds obtained will eventually be used for the welfare of the people by using various distribution methods. Bank Ziska in Ponorogo is an example of an amil zakat institution that has provided various kinds of economic development programs for the people and community empowerment, including giving cash to people who have been entangled in usury debt and cannot pay it, another program is to create an UMKM village that has was inaugurated by the Regent of Ponorogo, Sugiri 'Kang Giri' Sancoko in the MSME Village of Moneylender-Free Empowerment and the Digitalization of Bank Ziska Lazismu in Jintab Hamlet, Wonokerto Village, Jetis District 2021. for the national amil zakat institution.